Election Campaigns in Government Facilities, Places of Worship, and Education Units - Alif Wili Utama (Constitutionale)
The use of educational institutions for campaign activities is prohibited. In the application reviewed in Constitutional Court Decision Number 65/PUU-XXI/2023, it was argued that the Explanation of Article 280, paragraph (1), letter h could lead to constitutional harm for plaintiffs, both as voters and candidates for the DKI Jakarta Provincial DPRD. This harm arises from legal uncertainty concerning the prohibition of campaigns in government facilities, places of worship, and educational institutions. The legal uncertainty stems from a contradiction between the Article and its Explanation (contradictio in terminis). While Article 280, paragraph (1), letter h explicitly prohibits campaigns in these locations without exception, the Explanation contradicts this by allowing campaigns if they are invited by the responsible party and conducted without campaign materials. This discrepancy between two provisions—despite the Explanation not being a normative rule but rather a formulation of norms—creates ambiguity in the legal framework. This study employs library and normative research methods, examining legal materials from sources such as laws, court decisions, books, journals, and articles. The goal is to develop concepts and ideas related to campaign prohibitions from a democratic election perspective, drawing from the aforementioned literature.